Parents’ knowledge, attitude and practice of oral health and its association with oral health status of Arabic preschool children in the Klang Valley, Malaysia - Alsharif, Mohamed Khalid S (2020)
Oral health diseases among pre-school children such as tooth decay is a global public health problem and influence the overall health of children. Parental oral health knowledge, attitude and practice have a direct effect on pre-school children, since the pre-school children may not be able to fully express their emotions orally. This study aimed to determine the level of parents’ knowledge, attitude and practice of oral health and its association with the oral health status of pre-school children in Arabic pre-schools in Klang Valley, Malaysia. A cross-sectional study was conducted among pre-schoolers with proportional stratified sampling from selected five Arabic pre-schools. 400 self administered questionnaires in Arabic language were distributed among the Arabic parents. The questionnaire included five sections on sociodemographic characteristics, socioeconomic characteristics, parental oral health knowledge, attitude and practice, eating and oral hygiene habits of children and accessibility of dental services. The questionnaire had acceptable internal consistency (α=0.82). In this study, the internal consistency value was (α=0.78) and the test-retest reliability correlation coefficient showed a good reliability level (84%). SPSS version 23 was used to conduct Chi-Square test, Fisher’s exact test and binary logistic regression analysis for data analysis. Completed questionnaires were returned with a response rate of 95%. Among a total of 363 children with a median age of 4 years, 54.8% were females. Overall, 42.4% of the children had dental caries, 9.6% of them had gingivitis and 19.6% reported to have halitosis. Marital status, monthly income, accessibility to dental services, the gender of children, name of schools, start to brush the teeth and the number of times of brushing every day, visit the dentist regularly were factors significantly associated with the oral health status of children (p<0.05). Besides, parental knowledge, attitude and practice of oral health were significantly associated with the parent-reported oral health status of children (p<0.05). In conclusion, this study established that more than 50 % of the children found to have poor oral health. In order to mitigate these problems, effective oral health programs designed to change dietary habits and dental screening of children in this age group are necessary.